A novel ultrasonic wave-based analog Fourier transform computing system - Robert Frederik Diaz Uy; Viet Phuong Bui (AIP Advances, 2022)
The Fourier transform is a powerful tool that has manifold applications in various disciplines. With the rise of new applications, such as real-time image processing, there is a need for more efficient Fourier transformation methods. This has led to a number of advancements in the field of wave-based analog computing, with the development of the ultrasonic Fourier transform most recently. This paper presents an alternative design to existing ultrasonic Fourier transform analog computing systems, with its relative compactness being the main advantage. In this study, its capabilities and limitations are extensively examined.